Comparison of some physical and mechanical properties of CAD/CAM acrylic resins with heat-cured acrylic resins after exposure to artificial saliva (an in vitro study) - حربالي ولاء; محمود محمود; محمد سمير البرزاوي (Latakia University Journal -Medical Sciences Series, 2023)
The increase in water absorption of the acrylic dentures creates internal stress that eventually leads to the formation of cracks, which ultimately affects their mechanical properties, polymeric materials are generally stable structures with a high degree of resistance to biodegradation, however, several studies have shown that polymers biodegrade in the oral cavity. this study aims to compare the weight change (absorption and solubility) of CAD/CAM acrylic resin with conventional (heat cured) acrylic resin before and after immersion in artificial saliva (to simulate the oral cavity) in tow periods (one month, six months). the study sample included 32 samples of acrylic resin for both materials (16 conventional, 16 CAD/CAM), with dimensions of 20/20/1.5mm. the results of the statistical analysis of weight change (absorption and solubility) showed the lower means for CAD/CAM acrylic resin. we conclude within the limits of this study that the method of polymerization of CAD/CAM discs contributed to improved greater stability of weight over a period of one and six monthes of immersion in artificial saliva.